Development Model of Household Contacts as a Peer Support to Decrease the Prevalence of Pulmonary Tuberculosis - Suharyo, Suharyo; Mubarokah, Kismi (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
Tuberculosis is a global threat, caused mortality of 15 million people in 2014. Drug supervisor is the main strategy in patient adherence. Hence, the need for strengthening the strategy testing and counseling patients by a household contact as a peer support in overcoming the disease. Non randomized one-group pretest-posttest design was used. The identification of the characteristics of the household contact person who will be peer support was done through focus group discussions. Seventeen household contacts became a model of peer support that accompanied each individual patient. Differences in results were used the Wilcoxon test. There was a significant increase of knowledge (p value = 0.03), adherence (p value = 0.02), prevention practice of transmission by patients (p value = 0.03), and the prevalence of pulmonary TB was decreased by 41% after peer support intervention. PeerÃ‚Â Ã‚Â support model can be used as an alternative to increase the role of drug supervisor.